2020
DOI: 10.1007/s00441-020-03186-w
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of oxygen-sensing prolyl hydroxylases increases lipid accumulation in human primary tubular epithelial cells without inducing ER stress

Abstract: The role of the hypoxia-inducible transcription factor (HIF) pathway in renal lipid metabolism is largely unknown. As HIF stabilizing prolyl hydroxylase (PHD) inhibitors are currently investigated in clinical trials for the treatment of renal anemia, we studied the effects of genetic deletion and pharmacological inhibition of PHDs on renal lipid metabolism in transgenic mice and human primary tubular epithelial cells (hPTEC). Tubular cell-specific deletion of HIF prolyl hydroxylase 2 (Phd2) increased the size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…Other than the well-known effect of enhancing anaerobic glycolysis, studies have illustrated that HIF promotes lipid storage in liver and clear cell renal cell carcinoma (Rankin et al, 2009;Qiu et al, 2015;Du et al, 2017). Very recently, PHD inhibition was found to increase lipid accumulation in human tubular epithelial cells, suggesting participation of HIF in tubular lipid regulation, although the concrete mechanism still needs further investigation (Schley et al, 2020). We provide evidence that HIF1α activation has inhibitory effects on tubular lipid metabolism, including FAO, leading to lipid accumulation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Other than the well-known effect of enhancing anaerobic glycolysis, studies have illustrated that HIF promotes lipid storage in liver and clear cell renal cell carcinoma (Rankin et al, 2009;Qiu et al, 2015;Du et al, 2017). Very recently, PHD inhibition was found to increase lipid accumulation in human tubular epithelial cells, suggesting participation of HIF in tubular lipid regulation, although the concrete mechanism still needs further investigation (Schley et al, 2020). We provide evidence that HIF1α activation has inhibitory effects on tubular lipid metabolism, including FAO, leading to lipid accumulation.…”
Section: Discussionmentioning
confidence: 69%
“…The mechanisms mainly include induction of mitochondrial dysfunction, endoplasmic reticulum stress, apoptosis, and reactive oxygen species and proinflammatory factor production (Weinberg, 2006;Bobulescu, 2010;Bhargava and Schnellmann, 2017). HIF was recently found to be linked with renal tubular lipid accumulation, although further investigations are needed to reveal the concrete mechanism (Schley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Critically, we identified that a novel potential sensitive drug is dimethyloxallyl glycine (DMOG), a kind of prolyl hydroxylase inhibitor (PHI), may be able to treat invasive ovarian cancer. In terms of the association between DMOG and lipid metabolism, studies have found that DMOG can increase lipid accumulation in human primary renal tubular epithelial cells [41] and lipid absorption in macrophages [42]. erefore, DMOG may serve as a novel potential targeted drug for ovarian cancer.…”
Section: Identification Of Potential Targeted Drugs To High-scorementioning
confidence: 99%
“…It has been shown that lipotoxicity could contribute to the development of AKI and HIF could promote fatty acids accumulation in cells. However, in an experimental model of transgenic mice and human primary tubular epithelial cells, differing from cyclosporin treatment, the genetic deletion and pharmacological inhibition of PHDs (and thus the activation of the HIF system) did not cause cytotoxicity [ 49 ]. On the contrary, it may possibly protect tubular cells from toxic free fatty acids by trapping them as triacylglycerides in lipid droplets [ 49 ].…”
Section: The Hif System and Akimentioning
confidence: 99%